PENGARUH METODE CARD SORT TERHADAP PEMBENDAHARAAN KOSAKATA BAHASA ARAB SISWA KELAS VII MTS MIFTAHURRAHMAN TASIKMALAYA - Asep Ahmad A Munir (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2022)
Based on the findings and discussion, it was concluded that: 1) Scout Education Management focused onthe process of personality formation, life skills, and noble character scouts through KMD, KML, KPD, PitaranTrainers, KPL, Karang Pamitran, Mabi Orientation, Mainstay Courses, Saka Pamong Course , 2) there is still alack of qualified human resources both as trainers and mentors, Budget, implementation and stagnant curriculum,inadequate facilities, 3) Efforts to overcome problems, namely HR development, diversity curriculum, completingeducation programs, cadre of young trainers empowered in each course or orientation, self-identity of coaches andcoaches as good role models through among systems, and separation of positions.4) Conceptual and programmaticresults, the development of spiritual attitudes, social attitudes, and skills / abilities as human beings and citizens ofIndonesia in the context of Pancasila values and morality which are also called spiritual skills that practicereligious principles and implement the basic principles of Scouting and practice Pancasila, 5) Steps for futureimprovement are carried out by improving the image of trainers and coaches through activities with basicprinciples and scouting methods accompanied by 6 (six) integrated Sanusi value systems